India : towards anarchy (1967-1992) - Saksena, N. S. (New Delhi, 1993)
The present volume, discusses a wide range of subjects, including criminalisation of politics, corruption in the judicial system, failure of the bureaucracy, and the weakening of the police machinery, to highlight the fact that narrow political considerations of all political parties are leading the country to anarchy and chaos.
Keywords: Terrorism India 1967-1992